Clinically Precedented Protein Kinases: Rationale for Their Use in Neurodegenerative Disease - Benn, Caroline L.; Dawson, Lee A. (Frontiers in Aging Neuroscience, 2020)
Kinases are an intensively studied drug target class in current pharmacological research as evidenced by the large number of kinase inhibitors being assessed in clinical trials. Kinase-targeted therapies have potential for treatment of a broad array of indications including central nervous system (CNS) disorders. In addition to the many variables which contribute to identification of a successful therapeutic molecule, drug discovery for CNS-related disorders also requires significant consideration of access to the target organ and specifically crossing the blood-brain barrier (BBB). To date, only a small number of kinase inhibitors have been reported that are specifically designed to be BBB permeable, which nonetheless demonstrates the potential for success. This review considers the potential for kinase inhibitors in the context of unmet medical need for neurodegenerative disease. A subset of kinases that have been the focus of clinical investigations over a ten-year period have been identified and discussed individually. For each kinase target, the data underpinning the validity of each in the context of neurodegenerative disease is critically evaluated. Selected molecules for each kinase are identified with information on modality, binding site and CNS penetrance, if known. Current clinical development in neurodegenerative disease are summarized.